2021
DOI: 10.3389/fspas.2021.700579
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella Vulgaris Photobioreactor for Oxygen and Food Production on a Moon Base—Potential and Challenges

Abstract: A base on the Moon surface or a mission to Mars are potential destinations for human spaceflight, according to current space agencies’ plans. These scenarios pose several new challenges, since the environmental and operational conditions of the mission will strongly differ than those on the International Space Station (ISS). One critical parameter will be the increased mission duration and further distance from Earth, requiring a Life Support System (LSS) as independent as possible from Earth’s resources. Curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…This idea was expressed by K. Tsiolkovsky, who suggested that it is possible to use microalgae as a metabolic counterweight to humans during a long space flight or extraterrestrial settlements. Experiments have shown that in an ecosystem with closed gas and water loops, chlorella can provide a person with oxygen, absorbing carbon dioxide, and utilize the products of their vital functions for an almost unlimited time (the experiments lasted up to a year), but at the same time, a person cannot completely absorb the entire synthesized biomass of chlorella [ 210 ]. The advantages of using microalgae include the absence in the experiment of noticeable changes in the physiological and population state and side effects in the coexistence of humans and algae in closed systems, as well as high productivity (for chlorella, 25–30 L of oxygen from 1 L of suspension per day) and high the degree of reliability and stability of the algal link in providing adequate nutrition for the crew.…”
Section: Macroalgaementioning
confidence: 99%
“…This idea was expressed by K. Tsiolkovsky, who suggested that it is possible to use microalgae as a metabolic counterweight to humans during a long space flight or extraterrestrial settlements. Experiments have shown that in an ecosystem with closed gas and water loops, chlorella can provide a person with oxygen, absorbing carbon dioxide, and utilize the products of their vital functions for an almost unlimited time (the experiments lasted up to a year), but at the same time, a person cannot completely absorb the entire synthesized biomass of chlorella [ 210 ]. The advantages of using microalgae include the absence in the experiment of noticeable changes in the physiological and population state and side effects in the coexistence of humans and algae in closed systems, as well as high productivity (for chlorella, 25–30 L of oxygen from 1 L of suspension per day) and high the degree of reliability and stability of the algal link in providing adequate nutrition for the crew.…”
Section: Macroalgaementioning
confidence: 99%
“…Oxygen is an important parameter for the growth of microalgae and can be used as an indicator of ongoing photosynthesis. Like other photosynthetic organisms, C. vulgaris and S. armatus release oxygen into the environment [10][11][12]. Measures of the metabolic processes in microalgae cells include both the ability to produce oxygen and the level of its production.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the most applicable approach will strongly depend on the mission scenario, in terms of size, extent and duration. Reversible carbon scrubbers 23 combined with microbial conversion may enable a sustainable and near-closed process for deep space travel and exploration missions or initial human settlements 24 , 25 .
Fig.
…”
Section: Habitat Air Bioremediationmentioning
confidence: 99%